(NzB)QÆRNIK KOROTKOÇ FANTASTIKI (B" (NrUBÆKON (B" /s)E - (NmULQR(B, (N`(B.s ((N~ERN)QÆWCÆ (B:s)E [(NB(B. (NW(B.],s, 2010)
(NzB)QÆRKA WKL@^AÃ (B15 (NTWORÆW KOROTKOÇ SU^ASNOÇ FANTASTIKI(B, (NAWTORAMI QKIH Ã PISXMENNIKI uKRAÇNI(B, (NrOSÆÇ(B, æ(NZRAÇL@(B. (N{ÆSTX TWORÆW ÆZ ZBÆRKI NALEVATX AWTOROWÆ Z ~ERNÆWCÆW `RÆ@ mULQRU(B. (NkNIGA BUDE CÆKAWO@ WSÆM(B, (NHTO CÆKAWITXSQ SU^ASNO@ FANTASTIKO@(B.s)E
Keywords: (NhUDOVNQ L)QÆTERATURAs)E -- (NsW)QÆTOWAs)E -- (NpROZAs -- (NfANTASTIKAs -- (NzB)QÆRNIKI(B.s)E